Does family involvement matter in initial public offering underpricing? Evidence from Saudi Arabia - Dalal Alrubaishi; Ghadah Alarifi (International Journal of Management, Economics and Social Sciences (IJMESS), 2019)
The phenomenon of initial public offering (IPO) underpricing has been extensively researched in the literature, however, the underpricing of family firms has received little attention. This is even more prevalent when it comes to underpricing of family firms in an emerging market such as the Saudi Arabian market. This study explores the IPO underpricing phenomenon of firms that went public in the Saudi stock market with the aim of determining if there is any significant difference in underpricing between family and non-family firms. The study utilized prospect theory and stewardship theory as its theoretical framework and used family involvement in ownership and management as a proxy of family firms. Based on collected data set of first day trading price of 77 firms during 2007-2018 period and using ordinary least squares (OLS) hierarchical regression, the study found that family firms are negatively and significantly related to IPO underpricing. The study contributes to both family business and IPO underpricing literature by showing the effect of family involvement in stock valuation at the listing stage.
Keywords: G12; G24; G32; 330; Family firms; initial public offering; family involvement; underpricing; Saudi Arabia; emerging markets